Neuroprotective strategies in acute ischemic stroke: A narrative review of recent advances and clinical outcomes - Min Zhao; Yue Qiao; Alexander Weiss; Wenbo Zhao (Brain Circulation)
Reperfusion therapy, which substantially promotes the vessel recanalization rate and improves clinical outcomes, remains the most effective treatment of acute ischemic stroke (AIS). However, a substantial number of patients are either unsuitable for recanalization therapy or experience limited recovery postreperfusion. There is growing recognition that adjunctive neuroprotective therapies may further improve the outcomes in AIS patients by protecting brain tissue during ischemia. Recent advancements in neuroprotective approaches, including pharmacologic agents such as nerinetide edaravone, and uric acid, as well as nonpharmacological interventions, such as remote ischemic conditioning and normobaric hyperoxia, offer promising potentials in stroke care. This review provides an overview of the current neuroprotective therapies, examines recent clinical evidence, and discusses the strengths and weaknesses of certain clinical trials aimed at cerebral protection.